(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2013)
The aim of this paper is to analyse the salafi jihadist doctrine and the concept of jihad as interpreted by the followers of the Al Jama'ah Al Islamiyah movement. Because this movement adopts the concept of da'wah wal jihad to achieve its mission, this paper will discuss the different views that exist in defining the concept of jihad qital (revolutionary jihad). The paper also explores how the salafi jihadist ideology penetrated this movement and the key salafist scholars who influenced its views. Some of the scholars who reinterpreted the boundaries and requirements of jihad have close links with the followers of Al Jama'ah Al Islamiyah. These scholars reject the traditional limitations of jihad, particularly in relation to the killing of Muslims and non-Muslims. In this sense, this group promotes a broader and more aggressive concept of jihad. Finally, this paper identifies radical elements within Al Jama'ah Al Islamiyah that reject the traditional definition of jihad and redefine global jihad in an attempt to justify more aggressive actions and accept collateral damage to people of their own religion.